EXCLUSÃO, PODER E IDENTIDADE EM “VIDAS SECAS” - Nascimento , Francisco Alcides do (Linguagens, Educação e Sociedade, 1997)
The author of the text makes a Reading of Graciliano Ramos novel entitled “Vidas Secas” in the light of the concepts of exclusion, Power and identity. He discusses with the narrator the nation of power having as theoretical background Michel Foucault. The identity is seen as a contrition, a process and in is bases on Michael Pollack and Peter Burkes texts. Finally, exclusion has a reference the Brasilian reality.